2020
DOI: 10.1590/0103-6440202003663
|View full text |Cite
|
Sign up to set email alerts
|

12-Year Follow-Up of Regenerative Endodontic Treatment of Immature Permanent Upper Incisors with Acute Abscess

Abstract: This case report discusses the endodontic treatment of a 7-year-old girl who suffered trauma (intrusion) to the immature upper central incisors secondary to a fall from a bicycle. Thirty days after the accident the patient was brought by her mother for clinical and radiographic assessment with a chief complaint of swelling and tenderness to percussion and palpation. Acute apical abscess associated with immature teeth were diagnosed. A decision was made to perform regenerative endodontic treatment. Access cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In 2020, Maniglia-Ferreira et al [104] described a case of REP treatment of two central incisors with a 12-year follow-up. It consisted of 2.5% NaOCl, 17% EDTA, and 2% CHX gel used for disinfection (for one week), and then DAP was applied to one tooth and Ca(OH) 2 to the other (for three weeks).…”
Section: Comparison Of Methods and Effects Of Repmentioning
confidence: 99%
“…In 2020, Maniglia-Ferreira et al [104] described a case of REP treatment of two central incisors with a 12-year follow-up. It consisted of 2.5% NaOCl, 17% EDTA, and 2% CHX gel used for disinfection (for one week), and then DAP was applied to one tooth and Ca(OH) 2 to the other (for three weeks).…”
Section: Comparison Of Methods and Effects Of Repmentioning
confidence: 99%
“…Though most case reports and clinical studies have proved increased root length, thickened root wall and decreased size of apical foramen in immature teeth after REPs, 13 , 20 , 48 , 53 , 56 59 histological evaluation of the teeth treated with REPs have shown that the newly formed tissue were ectopic bone, cementum, and periodontal ligament instead of dental pulp or pulp-like tissue. 60 63 Animal studies have also confirmed the above results.…”
Section: Biological Foundation and Histological Evaluation Of Repsmentioning
confidence: 99%
“…In terms of regain of a positive response to pulp sensibility test after REPs, it was present in 50%~60% of published cases. However, researchers 33 , 48 suggested that positive response to pulp sensibility test in immature permanent teeth with pulp necrosis after REPs could not be taken as a proof of pulp regeneration, provided that by now no reorganized vital pulp tissue has been detected in the treated teeth, but just vital tissues containing cementum-like, bone-like tissue and nerve fibers. The vital soft tissues might be able to respond to pulp test to some degree probably because they are vascularized and innervated.…”
Section: Regenerative Endodontic Outcomesmentioning
confidence: 99%
See 2 more Smart Citations